LITERASI KEUANGAN DAN PENGGUNAAN APLIKASI PENCATATAN KEUANGAN TERHADAP PERILAKU FINANSIAL GEN-Z - Sally; Nopiani Indah (ITB AAS Indonesia Surakarta, 2026)
Generation Z has grown up in the digital era with easy access to e-commerce, digital wallets, and various online shopping platforms, making consumption activities more practical and efficient. While this convenience serves as a significant benefit of modern society, it may also become a potential drawback, as it can encourage consumptive behavior, such as impulsive buying and unplanned spending. This condition highlights the necessity of sound financial behavior in enhancing individuals’ ability to control and maintain their financial stability. This study seeks to examine the contribution of financial literacy and the use of financial recording applications on Generation Z’s approach to financial behavior. Based on discussions of the study, financial literacy and the use of financial recording applications positively influences Generation Z’s financial behavior. Therefore, the writer hopes this research can help Generation Z develop better financial management habits.